2014
DOI: 10.1186/1756-0500-7-584
|View full text |Cite
|
Sign up to set email alerts
|

Axillary and rectal thermometry in the newborn: do they agree?

Abstract: BackgroundAccurate measurement of body temperature is critical for the assessment of a newborn’s general well-being. In nursery settings, the gold standard rectal thermometry has been replaced by the axillary method. However, evidence pertaining to the agreement between axillary and rectal thermometry in the newborn is controversial. In this cross-sectional study, the agreement between axillary and rectal temperature in newborns, as well as the effects of neonatal, maternal and environmental factors on this ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 10 publications
3
17
0
Order By: Relevance
“…Similar results have been presented in later research, in which axillary temperatures were significantly lower than rectal temperatures for young children, infants and neonates (17)(18)(19). On the other hand, Charafeddine et al (10) found no significant difference between axillary and rectal temperature measurements in a sample of 118 infants.…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…Similar results have been presented in later research, in which axillary temperatures were significantly lower than rectal temperatures for young children, infants and neonates (17)(18)(19). On the other hand, Charafeddine et al (10) found no significant difference between axillary and rectal temperature measurements in a sample of 118 infants.…”
Section: Introductionsupporting
confidence: 85%
“…A Wilcoxon matched-pairs signed-rank test showed this difference to be significant (z = 11.1, p < 0.001). When the study population consists of neonates, age should be viewed in terms of gestational age as well as chronological age (10) The difference between axillary and rectal temperatures has been found to be lower during night-time (19) The body temperature of the patient has been found to correlate positively with the size of the difference between axillary and rectal temperatures (17,19) Incubator care has been found to create a stronger correlation between skin and rectal temperatures (20) Kangaroo care might be associated with larger temperature differences (20) The difference between axillary and rectal temperatures has been found to be larger for babies with Caesarean delivery (10) The sexr of the patient might also have explanatory value. The 95% confidence interval of the temperature difference was 0.356 AE 0.032.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are conflicting results regarding the accuracy and precision of axillary temperature [13,14,15]. However, it has been reported that in 108 term and preterm infants (29-41 weeks of gestation) who were clinically stable, the mean axillary (36.8 ± 0.4°C) and rectal (36.8 ± 0.5°C) temperatures were similar [16]. Although our study was randomised, the proportion of SGA infants was slightly higher in the axilla group, which may have rendered that group more susceptible to hypothermia.…”
Section: Discussionmentioning
confidence: 99%